2013
DOI: 10.5433/1679-0359.2013v34n6supl2p4015
|View full text |Cite
|
Sign up to set email alerts
|

Pork meat matured for different periods of time in vacuum-packaging system

Abstract: The objective of this study was to evaluate the quality of pork meat when matured. The treatments evaluated were: meat no maturated; meat matured for 3 days; meat matured for 6 days. The pH, water loss percentage, and liquid lost in thawing displayed a decreasing linear regression while the fluid lost in cooking showed an increasing linear regression. The L*, a*, b* and chroma showed an increasing linear effect while the tone displayed a decreasing linear regression. The mesophilic and psychrotrophic bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, during postmortem period, some meat quality parameters may be modified, e.g. pH, Water Holding Capacity (WHC), color and lipid oxidation (Tarsitano et al, 2013). The Meat freshness determines the choice of the product by the consumer (Xiong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during postmortem period, some meat quality parameters may be modified, e.g. pH, Water Holding Capacity (WHC), color and lipid oxidation (Tarsitano et al, 2013). The Meat freshness determines the choice of the product by the consumer (Xiong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the obtained results between goat and sheep meat we conclude that penetration force of cooked goat meat Vs cooked sheep meat before and after freezing was higher in all animal groups revealing more tenderness of goat meat. Tarsitano et al (2013) reported that during the period after full maturation, shear force may decrease due to proteolysis of the myofibrillar structural components. When WHC decreases, shear force was observed to increase.…”
Section: Discussionmentioning
confidence: 99%